2006
DOI: 10.4049/jimmunol.177.3.1661
|View full text |Cite
|
Sign up to set email alerts
|

Yeast β-Glucan Amplifies Phagocyte Killing of iC3b-Opsonized Tumor Cells via Complement Receptor 3-Syk-Phosphatidylinositol 3-Kinase Pathway

Abstract: Anti-tumor mAbs hold promise for cancer therapy, but are relatively inefficient. Therefore, there is a need for agents that might amplify the effectiveness of these mAbs. One such agent is β-glucan, a polysaccharide produced by fungi, yeast, and grains, but not mammalian cells. β-Glucans are bound by C receptor 3 (CR3) and, in concert with target-associated complement fragment iC3b, elicit phagocytosis and killing of yeast. β-Glucans may also promote killing of iC3b-opsonized tumor cells engendered by administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
149
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(154 citation statements)
references
References 40 publications
(34 reference statements)
4
149
1
Order By: Relevance
“…question as to whether the cholesterol-lowering effects are due to the differences in solubility is not relevant. The question of whether these effects are affected by solubility of glucans is pertinent however, since both soluble and insoluble glucans are processed by macrophages to an approximately 25-kDa active moiety that subsequently primes cells for biological activity (Hong et al, 2004;Li et al, 2006). The studies showing the results of in vivo glucan processing also invalidate the hypothesis of the importance of molecular weight of glucan (Bengtsson et al, 1989;Newman et al, 1992).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…question as to whether the cholesterol-lowering effects are due to the differences in solubility is not relevant. The question of whether these effects are affected by solubility of glucans is pertinent however, since both soluble and insoluble glucans are processed by macrophages to an approximately 25-kDa active moiety that subsequently primes cells for biological activity (Hong et al, 2004;Li et al, 2006). The studies showing the results of in vivo glucan processing also invalidate the hypothesis of the importance of molecular weight of glucan (Bengtsson et al, 1989;Newman et al, 1992).…”
Section: Discussionmentioning
confidence: 83%
“…Both these glucans and their activities are well documented (Yan et al, 2003(Yan et al, , 2005, including full toxicological assessment (Babicek et al, 2007), and are considered to be highly active glucans (Vetvicka et al, 2008). As the effectiveness of orally-administered glucans was fully established (Hong et al 2004;Li et al, 2006), glucans are currently nearing use in clinical practice. In addition, orally effective lentinan is already being used in Japan (Hamuro, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of β -glucan to enhance the activity of antitumor monoclonal antibodies (mAbs) also requires that they activate complement and deposit iC3b on tumor cells for recognition by CR3 on granulocytes and NK cells (Cheung and Modak 2002;Hong et al 2003). It has been demonstrated that β -glucan from both barley (Cheung and Modak 2002;Modak et al 2005) and yeast (Yan et al 1999;Hong et al 2003Hong et al , 2004Li et al 2006Li et al , 2007 has synergistic effects when used with anticancer mAbs in various tumor models. The mechanism of action has been explained in several studies (Hong et al 2003(Hong et al , 2004Li et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Orally administered high molecular weight β -1,3 glucans, such as glucan from baker's yeast and barley (Hong et al 2004), or small molecular weight β -1,3 glucans, such as laminarin (Rice et al 2005), go through an intermediate step in which they are taken up by gastrointestinal macrophages and shuttled to reticuloendothelial tissue and bone marrow. Once there, macrophages degrade large molecules of β -glucan into smaller biologically active fragments (Li et al 2006). The active fragments are slowly released from the macrophages, bind to mature bone marrow neutrophil or NK cell CR3, and prime these cells for targeted killing through the 3-Syk-phosphatidylinositol 3-kinase signaling pathway (Li et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation